Telemedicine use in orthopaedics: Experience during the COVID-19 pandemic. (June 2022) - Chin, Brian Z; Nashi, Nazrul; Lin, Shuxun; Yik, Kevin; Tan, Gamaliel; Kagda, Fareed HY
Introduction: With a recent resurgence of the 2019 coronavirus disease (COVID-19) cases globally, an increasing number of healthcare systems are adopting telemedicine as an alternative method of healthcare delivery in a bid to decrease disease transmission. Continued care of orthopaedic patients in the outpatient setting during the coronavirus disease of 2019 era can prove challenging without a systematic workflow, adequate logistics, and careful patient selection for teleconsultation. The aim of this paper is to describe our single-centre experience with the application of telemedicine in our orthopaedic practice, and its effectiveness in maintaining outpatient follow-up of orthopaedic patients. Methodology: We describe our centre's telemedicine model of care for orthopaedic patients on the outpatient follow-up – which includes workforce assembly, population health and target patients, logistics and communications, and overall workflow – with roles and responsibilities of involved people portrayed in detail. Results: Feedback from both patients and orthopaedic surgeons reflected high satisfaction rates with care provided, noting minimal communication and clinical barriers compared to face-to-face consultations. Whilst not without limitations, our protocol allowed for rapid adoption of telemedicine in line with a national-wide initiative to digitize healthcare. Discussion: The implementation of teleconsultation services at our orthopaedic centre has provided an effective method of healthcare delivery while enforcing social distancing measures – which proves vital in combating the spread of COVID-19 and ushering in a new normal.